Histidine-rich glycoprotein and idiopathic pulmonary fibrosis. Issue 12 (December 2015) - Ernst, G.; Dantas, E.; Sabatté, J.; Caro, F.; Salvado, A.; Grynblat, P.; Geffner, J.
Abstract: Histidine-rich glycoprotein (HRG) is an enigmatic glycoprotein able to interact with a variety of ligands such as IgG, complement components, heparan sulfate, thrombospondin, fibrinogen and plasminogen. HRG is present at high concentrations in plasma and there is evidence indicating that it is able to modulate the course of biological processes such as angiogenesis, fibroblast proliferation, complement activation, coagulation and fibrinolysis. Because these processes are involved in the pathogeneses of lung fibrosis we here analyzed a possible link between HRG and idiopathic pulmonary fibrosis (IPF). We found that plasma concentrations of HRG are significantly diminished in IPF patients compared to healthy subjects. Moreover, we found a positive correlation between HRG plasma levels and forced vital capacity (FVC) values, suggesting that plasma concentration of HRG would be a useful indicator of disease activity in IPF. HRG has been described as a negative acute phase reactant able to accumulate at sites of tissue injury. Hence, we also measured the concentrations of HRG in BAL samples from IPF patients. We found that the concentrations of HRG in samples from IPF patients were significantly higher compared to controls, suggesting that the reduced concentration of HRG in plasma from IPF patients could be due, at least in part, to an enhanced uptake of this protein in the lung. Highlights: Plasma levels of HRG are diminished in patients with IPF. A positive correlation exists between HRG plasma levels and forced vital capacity. Levels of HRG in BAL are higher in IPF patients compared with controls. The possible contribution of HRG to the pathogenesis of IPF remains unknown.